Consensus core outcome rating for the Japanese neonatal pain guidelines - Arimitsu, Takeshi; Ozawa, Mio; Gaughwin, Kaori (Frontiers in Pediatrics, 2023)
Introduction: The Japanese Neonatal Pain Guidelines Committee, led by the Japan Academy of Neonatal Nursing, uses the Grading of Recommendations, Assessment, Development, and Evaluation Working Group method to evaluate the quality of evidence and the strength of treatment recommendations. Currently, there are no reports on outcome ratings in neonatal pain guidelines. This study aimed to reach a consensus on the importance of outcomes through a guideline panel composed of doctors, nurses, nurse practitioner, physical therapist, and families to ensure consistency in systematic reviews of neonatal pain and future revisions to the guidelines. Methods: A total of 26 professionals including 21 medical personnel from clinical settings and academia and 5 parents from five family associations, participated in 3-stage eDelphi rounds. Results: The literature review and discussion identified 75 outcomes that were included in round one. The participants proposed three additional outcomes: 78 outcomes were scored in rounds two and three. Round three scores showed different stakeholder groups in terms of priority outcomes. Seventeen outcomes were included in the final core outcome and were considered critical for decision-making. Conclusion: Core outcomes of the development of neonatal pain guidelines in Japan were identified. The importance assessment process showed that the perspectives of medical providers and families on neonatal pain differed, and the importance of including family in the assessment as the spokesperson for the neonate admitted to the neonatal intensive care unit was evident.